2014
DOI: 10.1016/j.jiph.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Tularemia outbreaks in Kayseri, Turkey: An evaluation of the effect of climate change and climate variability on tularemia outbreaks

Abstract: A tularemia outbreak was observed between 2010 and 2012 with the initiation of rainy years. High temperature for a long period accompanied by low rainfall and low humidity may affect the vector's biology and initiate a tularemia outbreak in high plateaus in Kayseri Province and around.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 7 publications
1
33
0
2
Order By: Relevance
“…Recent publications from Turkey illustrate that the diagnosis may easily be overlooked because it often mimics other conditions of fever such as tuberculosis and other diseases that may cause enlarged lymph nodes (Karabay et al, 2013 ; Erdem et al, 2014 ; Yildirim et al, 2014 ). A presence of tularemia among humans in Iran's neighboring countries such as Azerbaijan (Clark et al, 2012 ), Armenia (Melikjanyan et al, 1996 ), and Turkey (Helvaci et al, 2000 ; Sahin et al, 2007 ; Balci et al, 2014 ) suggests that tularemia may be underdiagnosed in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications from Turkey illustrate that the diagnosis may easily be overlooked because it often mimics other conditions of fever such as tuberculosis and other diseases that may cause enlarged lymph nodes (Karabay et al, 2013 ; Erdem et al, 2014 ; Yildirim et al, 2014 ). A presence of tularemia among humans in Iran's neighboring countries such as Azerbaijan (Clark et al, 2012 ), Armenia (Melikjanyan et al, 1996 ), and Turkey (Helvaci et al, 2000 ; Sahin et al, 2007 ; Balci et al, 2014 ) suggests that tularemia may be underdiagnosed in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Observed and Projected Effects (6) Malaria in Portugal [89] Malaria in Germany [92] Malaria in Turkey [90] Aedes albopictus in Europe [98] Malaria in Spain [91] Recent and future Aedes albopictus suitability [99] WNF in Israel [93] Dengue in Europe [100] WNF in Hungary and Austria [94] Dengue in Europe [103] Chikungunya in Italy [96] Dengue and Chikungunya in Europe [101] Dengue in Madeira 2012 [102] Ticks transmit climate-sensitive infectious diseases including Crimean Congo hemorrhagic fever [108,109], Lyme borreliosis [110][111][112], tick-borne encephalitis [113][114][115][116][117][118][119][120] and Tularemia [121]. Several studies identified in the literature review do not report on climate change and tick-transmitted diseases, but instead describe changes in tick distribution, specifically in the United Kingdom [122], Slovenia [123], and the Czech Republic [124].…”
Section: Observed Effect (7)mentioning
confidence: 99%
“…In the last 20 years, its geographical range has expanded to, or been increasingly recognized in, new areas, and the known host range has expanded to include species not previously linked with tularemia, such as the red fox (Vulpes vulpes), the wild boar (Sus scrofa) and the raccoon dog (Nyctereutes procyonoides) [7][8][9][10]. Tularemia has also re-emerged in a number of locations, notably causing new human outbreaks in southern and central Europe in recent decades [11][12][13]. Tularemia is, therefore, considered to be a locally emerging and/or re-emerging infection in Europe.…”
Section: Introductionmentioning
confidence: 99%